(untitled) (GYMNASIUM, 2019)
In 1996, the Lega Calcio deal with RAI expired and the league signed deal with four media groups for 11 television packages, generating 100 million euro for the clubs. In mid 2000s the tv rights income reaches a 873 million euro for the 2005-06 season, with the Serie A tv rights annual income to gradually increase from a 844 million euro for the 2009-10 season to an amazing approximate 1,4 billion euro for the 2018-21 season. All these years Lega Calcio experimented a lot in the designing and application of a tv rights selling mechanism and its accompanied tv rights income distribution model. The study could be used by several professional football leagues, with the Greek Superleague being one of them, in order its higher management to evaluate the actions LFP undertook all these years and how these actions affected could be followed.